Dampak perubahan iklim terhadap produktivitas kelapa sawit (elaeis guineensis jacq) di PT Inti Indosawit Subur Desa Delima Jaya Koperasi Mulus Rahayu - Wandana, Fajar Aga; Hamid, Ardiansyah; Wahyuni, Sri; Dhora, Anna (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
The productivity of oil palm plants is influenced by environmental factors, namely climate, which plays an important role, so a study was carried out regarding the impact of climate change on oil palm productivity. This research is to produce palm oil productivity based on rainfall and temperature data. The research method uses correlation analysis and multiple regression. Correlation analysis functions to determine the relationship between air deficit and palm oil FFB productivity in accordance with the research data obtained and to determine the direction of the relationship that occurs. This data was analyzed using descriptive statistical methods and analyzed using multiple regression. From the research results it was concluded that: 1). Climate change (temperature) has a low relationship to palm oil productivity. Temperature does not have a significant effect on oil palm productivity. 2). The rainfall variable is 0.010 > probability 0.05, so it can be concluded that rainfall has a low relationship to Palm Oil Productivity, meaning that there is a significant influence between rainfall (X2) on Productivity (Y).